An exploratory study of the need for curriculum review of Master of Public Health Degree at a Rural-based University in South Africa - Takalani G. Tshitangano (AOSIS, 2016)
Background: Master of Public Health (MPH) training programmes were developed worldwide in response to the crisis in human resources for health. Aim: To determine whether the MPH programme at the selected rural-based university in South Africa enabled students to achieve the MPH core competencies relevant for Lower Middle Income Countries. Setting: The study was carried out at a rural-based University in South Africa. The target population was the 2011 first-year cohort of MPH students who by the beginning of 2014 had just completed their coursework. Methodology: A quantitative cross-sectional descriptive research design was adapted. Eighty-five students were randomly selected to participate in the study. A structured questionnaire comprising seven competency clusters was developed. The selected students completed a self-administered questionnaire. Only those students who signed consent forms participated in this study. The questionnaire was tested for construct validity and reliability using 10 students with similar characteristics to those sampled for the study. Microsoft Excel software was used to analyse the data descriptively in terms of frequency and percentages. Results: The students were confident of their competencies regarding public health science skills. Amongst these were analytical assessment, communication, community and intersectorial competencies as well as ethics. However, the students lacked confidence in contextsensitive issues, planning and management, research and development, and leadership competencies. Yet the latter is the backbone of public health practice. Conclusion and recommendation: There is a need for revamping public health curricula. In this respect, a follow-up study that builds a deeper understanding of the subject is needed.